A study on liquefaction of pretreated Mukah Balingian low rank Malaysian coal / Mohd Azlan Mohd Ishak - Mohd Ishak, Mohd Azlan (2007)
Direct liquefaction on untreated Mukah Balingian (MB) coal was successfully carried out at temperatures and pressures of 360 – 450 °C and 4 – 13 MPa, respectively, using tetralin as hydrogen-donor solvent. The coal conversion, oil+gas, asphaltene and preasphaltene obtained at maximum conditions of 450 °C, 4 MPa, 30 min reaction time, 1:10 coal-to-solvent ratio and with stirring, were 90%, 80%, 7% and 2%, respectively. It was observed that heat plays an important role in comparison to pressure in contributing to high coal conversion and oil+gas yield, and these results are well correlated with the high content of reactive macerals. In this study, three types of pretreatments were applied on MB coal, i.e. solvent swelling, in-situ solvent soaking and heating (SSH) and microwave irradiation. In the solvent swelling pretreatment, higher swelling ratio, coal reactivity and volatile yield (Ei) were obtained when swelled in mixed solvents followed, in decreasing order, by single solvents and untreated coal. The Ei decreased from untreated coal followed by single and mixed solvents. The synergistic effect of mixed solvent swelling was attributed to good interactions between the solvent and coal reactive sites, which promoted the breaking of H-bonds in coal and eventually weakened the coal-coal macrostructure. Oil+gas yield obtained from liquefaction on the mixed solvent-swelled samples showed further enhancement at temperatures from 360 – 450 °C and reached a maximum value at 420 °C. In the SSH pretreatment, the DTG results of the pyrolysed SSH-treated coals showed the presence of highly volatile matter released at 150 – 200 °C, which was attributed to the tetralin incorporated within the coal macrostructure. The coal conversion and oil+gas yield obtained from the liquefaction of SSH-pretreated coals under various pretreatment conditions at 420 °C showed an increased of up to 7 and 12%, respectively, and was comparable to that of untreated sample at 450 °C, although the higher molecular weight preasphaltene also showed an increase.